(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Faisal TM, Akbar H, Putriningtias A, Putra SA. 2019. Short Communication: Community structure of prawns (Decapoda: Penaeidae and Palaemonidae) in mangrove inlets of Kuala Langsa, Aceh, Indonesia. Biodiversitas 20: 1306-1311. The aim of this research is to describe the structure of prawn community that found at mangrove inlets of Kuala Langsa (Aceh, Indonesia). The survey was done in August 2018. Sampling sites were defined as arbitrarily. Scope netting (mesh size 1 cm and diameter 100 cm) was used to sample the prawn community. Samples were analyzed and stored at The Primary Laboratory of Universitas Samudra, Kota Langsa, Aceh. Five species of prawns from two families (i.e., Decapoda: Penaeidae and Palaemonidae) were found, i.e., Penaeus monodon, Penaeus indicus, Metapenaeus monoceros, Penaeus vannamei, Palaemon sp. The most dominance species found is M. monoceros, and the most infrequently species found is Palaemon sp. Prawn community between sampling sites are found in a high level of similarity, with medium diversity and evenness index, and no dominance indicated.